2022
DOI: 10.1002/cre2.666
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial PD‐L1 expression at tumor front predicts overall survival in a cohort of oral squamous cell carcinomas from Sudan

Abstract: Background We recently described the tumor immune microenvironment (TIME) in oral squamous cell carcinomas (OSCC) from Sudan by assessing the core of the lesions. However, the invasive tumor front (ITF) is the most active part of OSCC lesions; thus, TIME should also be characterized at the ITF in this patient cohort. Objectives We aimed to evaluate patterns of immune cell infiltration at the ITF in a cohort of OSCC patients from Sudan previously investigated at the tumor center and their association with clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…However, 2 studies have reported findings that contradict our findings. Spector et al and Gaafar et al, reported that higher CD4 + cell counts were associated with advanced-stage OSCC [ 41 , 46 ]. Additionally, the study by Gaafar et al found that dense CD4 + cell infiltrate was associated with poorly differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 2 studies have reported findings that contradict our findings. Spector et al and Gaafar et al, reported that higher CD4 + cell counts were associated with advanced-stage OSCC [ 41 , 46 ]. Additionally, the study by Gaafar et al found that dense CD4 + cell infiltrate was associated with poorly differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sales de Sa et al found that increased CD4 + expression tended to have a worse prognosis in OSCC, but this result was not significant and the study only included 48 participants [ 37 ]. Gaafar et al found that dense CD4 + cells were associated with worse OS, although it is important to note that the median follow-up time for the study was relatively short (48 months), and the sample size was relatively small ( n = 22) [ 46 ]. At this time, we are unclear about these inconsistent CD4 expression results in OSCCs, however CD4 + cells are able to differentiate into different subsets such as Th1, Th2, Th9, Th17, Th22, Tregs, and Tfh (follicular helper T cells) which all have different roles.…”
Section: Discussionmentioning
confidence: 99%